Heidegger's technologies : postphenomenological perspectives - Ihde, Don, 1934- (Perspectives in continental philosophy., 2010)
Heidegger is the only thinker of his generation whose philosophy of technology is still widely read today. This book not only serves as an introduction to Heidegger's philosophy of technology, it also indicates a postphenomenological counter-strategy for technological analysis.